2021
DOI: 10.3390/medicina57010045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sevoflurane on Lewis Lung Carcinoma Cell Proliferation In Vivo and In Vitro

Abstract: Background and objectives: There are several studies that sevoflurane could enhance proliferation of cancer cells, while others suggest no effect on clinical outcome. We conducted in vivo and in vitro experiments to investigate the effects of sevoflurane, a volatile anesthetic, on proliferation and outcomes of Lewis lung carcinoma (LLC) cells. Materials and Methods: A total of 37 mice were injected with LLC cells to compare the tumor size and survival of the sevoflurane exposed group (sevo group) and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Volatile anesthetics not only cause immune cell dysfunction but apoptosis of neutrophils and T-lymphocytes ( 38 , 39 ), as sevoflurane, one of the most commonly used inhalation anesthetics, induces apoptosis and oxidative stress in lymphocytes ( 40 ). In another study, although there were no significant differences in tumor size or survival between sevoflurane and control mice, in vitro study showed that the proliferation of Lewis lung carcinoma cells exposed to sevoflurane increased by 9.2% compared to the controls ( 41 ). This implies that sevoflurane exposure might enhance the proliferation of tumor cells in vitro environment, but might not affect proliferation in vivo , suggesting that the effects of anesthetics on in vitro studies of cancer do not necessarily translate into in vivo or clinical studies.…”
Section: Perioperative Factors Associated With Cancer Promotionmentioning
confidence: 92%
“…Volatile anesthetics not only cause immune cell dysfunction but apoptosis of neutrophils and T-lymphocytes ( 38 , 39 ), as sevoflurane, one of the most commonly used inhalation anesthetics, induces apoptosis and oxidative stress in lymphocytes ( 40 ). In another study, although there were no significant differences in tumor size or survival between sevoflurane and control mice, in vitro study showed that the proliferation of Lewis lung carcinoma cells exposed to sevoflurane increased by 9.2% compared to the controls ( 41 ). This implies that sevoflurane exposure might enhance the proliferation of tumor cells in vitro environment, but might not affect proliferation in vivo , suggesting that the effects of anesthetics on in vitro studies of cancer do not necessarily translate into in vivo or clinical studies.…”
Section: Perioperative Factors Associated With Cancer Promotionmentioning
confidence: 92%
“…During the experimental period, the tumor size and mouse weight were measured. The length and width of the tumor were measured by a caliper and the tumor volume was calculated as follows [ 14 , 15 ]: tumor volume (cm 3 ) = length × width 2 × 0.5 …”
Section: Methodsmentioning
confidence: 99%
“…Some studies suggest a possible link between sevoflurane exposure and increased risk of cancer recurrence and mortality in patients undergoing cancer surgery [ 6 , 7 ]. Other studies have not found any significant association [ 14 ]. It is important to note that cancer development is a complex process that involves many factors, including genetic predisposition, lifestyle, environmental exposure, and other medical conditions.…”
Section: Introductionmentioning
confidence: 90%
“…Isoflurane activates the Akt-mTOR signaling pathway; further, it promotes proliferation, migration, and invasiveness of NSCLC cells, resulting in pro-tumor effects [15]. Exposure of Lewis lung carcinoma cells to sevoflurane promotes cell proliferation in vitro [28]. However, another in vitro study reported that sevoflurane exerts antitumor effects by inhibiting the proliferation and invasion of lung adenocarcinoma cells and enhancing apoptosis by regulating the long chain RNA PCAT6/miR-326/Wnt5a/β-catenin axis [29].…”
Section: Contrastingly a Few Studies Have Reported That Inhalation An...mentioning
confidence: 99%